The Use of Protective Ventilation in Post-COVID Respiratory Failure - Koltunova, Hanna B.; Voitiuk, Vitalii V.; Chyzh, Kostiantyn P. (Ukrainian Journal of Cardiovascular Surgery, 2021)
Implementation of the principles of protective ventilation in the intensive care of respiratory failure in patients after COVID-19 can improve the results of treatment of patients with cardiosurgical abnormalities, namely the implementation of surgical treatment in the post-COVID-19 period. The widespread occurrence of coronavirus disease 2019 (COVID-19) in the world has led to a sharp decrease in the number of cardiac surgeries and had a negative impact on treatment outcomes. Case description. Patient P., 62 years old, underwent examination and treatment from February 18 to March 3, 2021 at the National Amosov Institute of Cardiovascular Surgery of the National Academy of Medical Sciences of Ukraine with a diagnosis of infective endocarditis of the aortic valve. Aortic insufficiency. Acute heart failure. Grade III respiratory failure. Condition after bilateral polysegmental COVID-19 pneumonia, chronic obstructive pulmonary disease, GOLD 2. After aortic valve replacement, plasty of aortic root abscess due to infective endocarditis of the aortic valve, the patient was admitted to the intensive care unit for further treatment. In the postoperative period, respiratory failure was observed. Given the COVID-19 pneumonia, mechanical ventilation was performed according to the recommendations for protective ventilation. The duration of mechanical ventilation was 72 hours, followed by a successful transition to self-breathing. Conclusions. Given the initial condition of the patient with COVID-19 pneumonia, protective lung ventilation is reasonable after cardiac surgery. This issue needs further study.